DETERMINASI ILMU HUKUM DI PANGGUNG JUS DICERE: SEBUAH TITIK AKHIR POTRET GENEOLOGIS DARI MEDAN PENGOLAHAN HUKUM PRAKTIS, INTRAYUDISIAL DAN EKSTRAYUDISIAL - Herman Bakir (Jurnal Ilmu Hukum, 2019)
AbstractThis paper aims to theoretically describe a genealogical feature of science which because of itsown orientative profundity has received the awarding of the title of the legal theory as “the authentic legal science”, namely: science of law, especially by looking at the activities that this science has done in forums Jus Dicere. The method used in this descriptive effort is called normative-theoretical, while the starting point (approach) is a juridical-interdisciplinary way of looking of Legal Theory, especially while this theoretical discipline must theorize the genetic potential of science of law itself. The results of this study are: (a) Genetically, science of law is a science that can separate itself into the family of engineering sciences, and the genuine science of law at this belief is Legal Engineering; (b) Jus Dicere is a much wider area than Jus Dare, as a place where the science of law demonstrates all itsown potential, or expertises/skills as an engineering sciences and technology; (c) in this capacity, the science of law does not merely appear as a Technique of Legislative Drafting (Jus Dare); but also as an Technique of Investigation; Technique of Prosecution; Technique of Adjudication; Technique of Notaryship; Technique of Court Proceedings; Advocacy Techniques for Criminal Law Cases; etc (Jus Dicere). The theoretical explanations related to geneology, as well as the daily tasks of science of law are important, especially in relation to the development of the disciplinary paradigm of the science that we call the science of law. Finally, however, this paper wants to promise its readers a more convincing theoretical insight regarding the theoretical knowledge of science of law, whether it is at the state of inactive, or when it is in motion. Keywords: The Science of Law, Family of Engineering Science, Legal Technique, The Stage of Jus Dicere AbstrakArtikel ini dimaksudkan untuk secara teoretis mendeskripsikan sebuah fitur geneologis dari ilmu yang karena kedalaman orientatifnya telah menerima penganugerahan Teori Hukum sebuah gelar sebagai “the authentic legal science”, yakni: Ilmu Hukum, terutama dengan memperhatikan kiprah ilmu disebutkan terakhir di forum-forum Jus Dicere. Metode dalam usaha deskriptif ini adalah normatif-teoretikal, sedangkan titik-tolaknya (pendekatannya) adalah cara melihat yang yuridis-interdisipliner dari Teori Hukum, terutama selagi disiplin ilmu teoretis ini harus berteori dengan sisi geneologis dari Ilmu Hukum itu sendiri. Hasil penelitian: (a) secara genetikal, llmu Hukum adalah ilmu yang mengelompokkan diri ke dalam keluarga ilmu-ilmu teknikal, dan oleh karenanya Ilmu Hukum yang sesungguhnya itu dengan bertolak dari keyakinan ini disebut “Teknik Hukum”; (b) Jus Dicere merupakan lahan yang jauh lebih luas di banding Jus Dare, tempat di mana Ilmu Hukum mendemonstrasikan segenap potensi, atau keahlian/keterampilan teknisnya sebagai suatu ilmu yang mandiri secara disipliner; (c) dalam terminologi ini (Teknik Hukum), llmu Hukum tidak sekedar tampil sebagai Teknik Perundang-undangan (Jus Dare); tapi juga sebagai Teknik Penyidikan; Teknik Penuntutan; Teknik Kehakiman; Teknik Kenotariatan; Teknik Beracara; Teknik Advokasi; dan lain sebagainya (Jus Dicere). Akhirnya, bagaimanapun tulisan ini ingin menghadirkan kepada pembacanya sebuah wawasan teoretis yang lebih meyakinkan terkait pengetahuan-pengetahuan teoretis tentang Ilmu Hukum, baik saat diam, ataupun saat bergerak. Kata Kunci: Ilmu Hukum, Keluarga Ilmu Teknikal, Teknik Hukum, Panggung Jus Dicere